A study to determine the effect of nano-selenium and thymoquinone on the Nrf2 gene expression in Alzheimer’s disease - Doha El-Sayed Ellakwa; Laila Ahmed Rashed; Ola Sayed Ali; Noha Amr El-Sabbagh (Future Science OA)
Introduction Alzheimer’s disease is a developing public health concern in aging communities that affects a sizable section of the global population. The risk of Alzheimer’s disease increases with age; it affects one-third of males and two-thirds of women. This research attempts to assess the effect of nano-selenium and thymoquinone on Nrf2 gene expression levels in Alzheimer’s disease (AD).Methods There were five identical groups of 50 albino male rats: a control group that was healthy; an AD positive control group; an AD group that received nano-selenium (5 mg/kg); an AD group that received thymoquinone (2 mg/kg); and an AD group that received both. The duration of treatment was 4 weeks. The levels of Nrf2 in brain tissues were evaluated using real-time PCR.Results Nrf2 mean expression levels in the nano-selenium-treated rats, the thymoquinone-treated rats, and the rats that were given both treatments all increased significantly compared to AD rats with no treatment.Conclusions This study showed that nano-selenium and thymoquinone elevated Nrf2 gene expression levels in AD.